The Influence of Competence on Employee Performance at the Office of Education and Culture of Enrekang District - Serli; Muh. Ichwan Musa; Uhud Darmawan Natsir; Burhanuddin; Nurman (Economics and Business Journal (ECBIS), 2023)
This study aims to determine the effect of competence on employee performance at the Education and Culture Office of Enrekang Regency. The independent variable in this study is employee competency, while the dependent variable is employee performance. This type of research is quantitative research. The number of respondents used in this study were 30 people. The data analysis technique used in this study is simple linear regression analysis using SPSS 13.00 for windows. The results of this study were obtained from the t test showing a significant influence between the two variables with a sig probability. of 0.009 where this value is much smaller than 0.05. This means that competence has a significant influence on employee performance. Because the significant value is smaller than the error rate (0.05). The conclusion is that employee competence has a positive and significant effect on employee performance at the Education and Culture Office of Enrekang Regency.